War, Peace, and Religion's Biocultural Evolution - Burhoe, Ralph W. (Zygon, 1986)
Abstract. A recent scientifically and historically grounded theory on human genetic and cultural evolution suggests why the religious elements of culture became the primary source of both peaceful cooperation within societal ingroups and at the same time of destructive wars with outgroups. It also describes the role of religion in the evolution of ape-men into humans. The theory indicates why human societal life is not long viable without the underpinning of a healthy, noncoercive, religious faith; why sound religious faith is weak now; and why we may hope both for better morals and for worldwide cooperation in peace.